A new reduced chalcone-derivative affects the membrane permeability and electric potential of multidrug-resistant Enterococcusfaecalis. (25th September 2022) - Tempone, Andre Gustavo; Theodoro, Reinaldo dos Santos; Romanelli, Maiara Maria; Santos Ferreira, Dayana Agnes; Amaral, Maiara; Ribeiro de Assis, Leticia; Santa Cruz, Lucas Monteiro; Costa, Alan Roberto; Zanella, Rosemeire Cobo; Christodoulides, Myron; Regasini, Luis Octavio; Camargo, Carlos Henrique
Abstract: The emergence and spread of multidrug-resistant (MDR) enterococci and other Gram-positive bacteria represents a severe problem due to the lack of effective therapeutic alternatives. Natural products have long been an important source of new antibacterial scaffolds and can play a key role in the current antibiotic crisis. Enterococci are predominantly non-pathogenic gastrointestinal commensal bacteria, but among them, Enterococcus faecalis and Enterococcus faecium represent the species that account for most clinically relevant infections. The emergence of MDR enterococci has reduced the available antibiotic treatment options and highlights the need to develop new antimicrobial compounds. In the search for new hit compounds against MDR Enterococcus spp., natural-derived compounds represent inspiring scaffolds for drug design studies. In this work, the antimicrobial activity of a fully synthetic chalcone derivative (r4MB) was determined on a clinical panel of 34 MDR Gram-positive bacteria, mostly constituted by E. faecalis and E. faecium, along with Staphylococcus spp., amongst others. Compound r4MB showed activity against 100% of the tested strains, with the minimum inhibitory concentration (MIC) in the range of 5–20 μM. The lethal action of the compound was evaluated using different fluorescent-based assays. The compound showed a time-dependent permeabilisation of the membrane of a vancomycin-resistant E. faecalis, detected by the fluorescent probe SYTOX Green, and digital fluorescent microscopy corroborated the spectrofluorimetric analysis within 6 min of incubation. Flow cytometry analysis of the membrane electric potential demonstrated a significant depolarization, confirming the target of the compound towards the bacterial membrane. No cytotoxic haemolysis was observed with mammalian erythrocytes, and a 99% cytotoxic concentration of 118 μM on NCTC cells demonstrated a promising antimicrobial selectivity. In silico studies using SwissADME and ADMETLabs servers suggest that compound r4MB displayed adequate ADME properties, with no alerts for pan-assay interference compounds (PAINS). Future hit-to-lead optimization of this chalcone derivative can contribute to developing a more potent derivative against infections caused by MDR enterococci. Graphical abstract: Image 1 Highlights: A chalcone derivative was activity in a panel of multidrug resistant bacteria. Minimal Inhibitory Concentration was in a range of 5–20 μM. The compound induced permeabilisation of the membrane of E. faecalis. The compound caused depolarization of the membrane. The compound induced no hemolysis to erythrocytes.